PENGARUH BUDAYA ORGANISASI, KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PT BANK MANDIRI (PERSERO) Tbk KANTOR CABANG PEMBANTU PRINGSEWU - Kohar Kohar (Jurnal Ilmiah Ekonomi Manajemen: Jurnal Ilmiah Multi Science, 2018)
Performance is shown as a behavior resulting performance by employees in various roles in the company's work. Thus, companies can through various approaches in order to improve the performance of employees among the organizational culture, compensation and create a conducive working environment.The purpose of this study was to determine: (1) the influence of organizational culture on employee performance (2) the effect of compensation to employee performance (3) the impact of work environment on employee performance (4) the influence of organizational culture, compensation and working environment together on performance employees at PT Bank Mandiri (Persero) Tbk Branch Office Pringsewu.This research uses descriptive design verification, with a sample of 46 employees at PT Bank Mandiri (Persero) Branch Office Pringsewu. Data is collected using questionnaires and documentation, then the data were analyzed using multiple linear regression. The results showed: (1) There is a positive and significant influence of organizational culture on employee performance, meaning that if the employee's performance will be improved, the one that can be taken is to promote a culture of good organization. (2) There is a positive and significant impact on the performance employee compensation, meaning that if the employee's performance will be improved, the one that can be taken is to improve the implementation of good compensation. (3) There is a positive and significant impact on the performance of the work environment of employees,, meaning that if the employee's performance will be improved, the one that can be taken is to develop a good working environment. (4) The organizational culture, compensation and working environment together affect the performance of employees at PT Bank Mandiri (Persero) Tbk Branch Office Pringsewu. This means that if the organizational culture, compensation and working environment together improved the performance of employees will also increase.Keywords: Organizational Culture, Compensation, Work Environment,  Performance